Metastasis of a Renal Collecting Duct Adenocarcinoma to the Oral Cavity After Tooth Extraction. Issue 4 (June 2017) - Erkilic, Suna; Keskinruzgar, Aydin; Bozdag, Zehra; Gunhan, Omer
Abstract : Abstract: Metastatic tumors rarely occur in the oral cavity. The most common of the oral metastases are lung cancers in males, and breast and genital cancers in females. The most common primary tumor metastasis to the oral cavity is from the lung, kidney, liver, prostate, and colorectal cancers. The metastatic lesions are similar to oral lesions such as pyogenic granuloma, giant cell lesions, gingival polyps, hemangioma, peripheral fibroma, and adenoid squamous cell carcinoma. Therefore, the diagnosis of primary tumors is challenging. To our knowledge, this is the first reported case to feature metastasis of a renal collecting duct adenocarcinoma to the oral cavity after tooth extraction.